EXPLORING CULTURAL DIFFERENCES IN HEADLINE WRITING IN THE ENGLISH AND UZBEK PRESS - Mirzayeva Gulasal Ergashovna; Fayzullayeva Uldona Boybo’riyevna (TADQIQOTLAR, 2025)
Abstract. This article examines the stylistic elements present in the media language of English  and  Uzbek,  concentrating  on  aspects  such  as  brevity,  figurative  language, structural  organization,  and  the  balance  between  objectivity  and  engagement.  The results indicate that English media prioritizes conciseness through succinct syntax and straightforward headlines, whereas Uzbek media leans towards a more formal tone with  contextual  depth,  influenced  by  cultural  norms.  The  practical  results  of  this research  advocate  for  improved  journalism  education,  translation  practices,  and multilingual  content  strategies.  Additionally,  the  social  implications  highlight  how these stylistic variations affect public discourse, the accessibility of information, and trust levels within different linguistic and cultural settings, thus highlighting the need for targeted media literacy programs. The purpose of this study is to explore the cultural differences in advertising between Uzbek and the Great Britain. Two different samples of  print  magazine  advertisements  were  taken  from  beauty  magazines  published  in Uzbek and English to determine how much, if any, localization is occurring in Uzbek media.